2010
DOI: 10.1039/c0cc02162h
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic ignition of ionic liquids for propellant applications

Abstract: In this proof of concept study, the ionic liquids, 2-hydroxyethylhydrazinium nitrate and 2-hydroxyethylhydrazinium dinitrate, ignited on contact with preheated Shell 405 (iridium supported on alumina) catalyst and energetically decomposed with no additional ignition source, suggesting a possible route to hydrazine replacements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 16 publications
0
29
0
1
Order By: Relevance
“…19À24 It was recently found that a set of three different solvatochromic probes is sufficient to determine precise α, β, and π* (the dipolarity/ polarizability) À values of ILs. 19À23 The dissolved solvatochromic 4 shows the high hydrogen bonding accepting ability of the azolate anion and therefore the high probability of hydrogen bonding. The fact that the α parameter is considerably higher for [Bmim]5AT than for [Bmim]4Ni-Im indicates higher strength of interaction in [Bmim]5AT due to its superior electron density in the nitrogenrich ring.…”
Section: Lettermentioning
confidence: 99%
“…19À24 It was recently found that a set of three different solvatochromic probes is sufficient to determine precise α, β, and π* (the dipolarity/ polarizability) À values of ILs. 19À23 The dissolved solvatochromic 4 shows the high hydrogen bonding accepting ability of the azolate anion and therefore the high probability of hydrogen bonding. The fact that the α parameter is considerably higher for [Bmim]5AT than for [Bmim]4Ni-Im indicates higher strength of interaction in [Bmim]5AT due to its superior electron density in the nitrogenrich ring.…”
Section: Lettermentioning
confidence: 99%
“…EILs based on 2-hydroxyethyl hydrazine were found to be thermally stable and less hazardous than hydrazine [12]. One such EIL, hydroxyethylhydrazinium nitrate (HEHN), was found to be a suitable candidate for the replacement of hydrazine-based monopropellants [13]. Although HEHN was not hypergolic at room temperature with nitric acid, hypergolicity may be imparted by suitable measures, such as the addition of water and acetone, and catalysing the oxidizer with 1 to 3 mole percent nickel nitrate, along with preheating the fuel and oxidizer to 394 K [14].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several general reviews published on protic ionic liquids, with a few provided here . Specifically, within the space community, protic ionic liquids (and related salts) are being proposed as chemical thruster propellants, with several candidates, including hydroxylammonium nitrate, ammonium dinitramide, and 2‐hydroxyethylhydrazinium nitrate (HEHN), being considered.…”
Section: Introductionmentioning
confidence: 99%